A Project Report on Condiyional Anonymity With Traceability in Wireless Mesh Networks - POORNIMA P, PREETHI E, SHALINII P and SUMANTH K P (2011)
INTERNAL GUIDE : Preethi Sheba Hepsiba EXTERNAL GUIDE : Avayambal K USN NO : 1MJ08CS061, 1MJ08CS067, 1MJ08CS084 and 1MJ08CS416 CARRIED OUT AT : Mvj Coolege Of Engineerig Channasandra Near ITPB Bangalore-560 067 ACC NO : PR1840
Keywords: Networks